Synthesis and Natural Distribution of Anti-inflammatory Alkamides from Echinacea - Kraus, George A. (MDPI, 2006)
The synthesis of the alkamides 2Z,4E-undeca-2,4-dien-8,10-diynoic acid isobutyl amide (1) and 2Z,4E-undeca-2,4-dien-8,10-diynoic acid isobutyl amide (5) was accomplished by organometallic coupling followed by introduction of the doubly unsaturated amide moiety. The distribution of these two amides in accessions of the nine species of Echinacea was determined.